Laboratory observations of time‐dependent frictional strengthening and stress relaxation in natural and synthetic fault gouges. Issue 2 (19th February 2016) - Carpenter, B. M.; Ikari, M. J.; Marone, C.
Abstract: Interseismic recovery of fault strength (healing) following earthquake failure is a fundamental requirement of the seismic cycle and likely plays a key role in determining the stability and slip behavior of tectonic faults. We report on laboratory measurements of time‐ and slip‐dependent frictional strengthening for natural and synthetic gouges to evaluate the role of mineralogy in frictional strengthening. We performed slide‐hold‐slide (SHS) shearing experiments on nine natural fault gouges and eight synthetic gouges at conditions of 20 MPa normal stress, 100% relative humidity (RH), large shear strain ( 15), and room temperature. Phyllosilicate‐rich rocks show the lowest rates of frictional strengthening. Samples rich in quartz and feldspar exhibit intermediate rates of frictional strengthening, and calcite‐rich gouges show the largest values. Our results show that (1) the rates of frictional strengthening and creep relaxation scale with frictional strength, (2) phyllosilicate‐rich fault gouges have low strength and healing characteristics that promote stable, aseismic creep, (3) most natural fault gouges exhibit intermediate rates of frictional strengthening, consistent with a broad range of fault slip behaviors, and (4) calcite‐rich fault rocks show the highest rates of frictional strengthening, low values of dilation upon reshear, and high frictional strengths, all of which would promote seismogenic behavior. Key Points: Frictional restrengthening is a fundamental requirement of the earthquake cycle Performed carefully controlled experiments on 17 natural and synthetic gouges Gouge mineralogy exerts significant control on healing behavior and mode of slip